A Class-E high-voltage pulse generator for ultrasound medical imaging applications. (June 2020) - Tu, Steve Hung-Lung; Tsai, Po-Yu
Abstract: A Class-E high-voltage IC pulse generator which can be employed in front-end transducers for MEMS ultrasound medical imaging applications is investigated in this paper. The high drain-to-source voltage stress is reduced by the employment of the self-biased cascode configuration. Experimental IC measurement results demonstrate that the self-biased cascode configuration can generate over 36-V high voltage pulses with a 5-Vpp input triggering signal from a 5-V supply voltage at a broad range of output capacitive loads for 32-MHz MEMS ultrasound transducer.